Meditation: Evidence Map of Systematic Reviews - Schlechta Portella, Caio Fábio; Ghelman, Ricardo; Abdala, Veronica; Schveitzer, Mariana Cabral; Afonso, Rui Ferreira (Frontiers in Public Health, 2021)
Study Basis: This evidence map presents a summary of studies that addressed the effects of meditation on various clinical and health conditions. Meditation is a contemplative practice that has been used for the promotion of health, and the treatment of different conditions. Method: The study is based on the search of four electronic databases for the period 1994-November 2019 and includes systematic reviews, meta-analyses, meta-syntheses, and integrative reviews. 3iE evidence gap map was the methodology of choice, and AMSTAR 2 was used for the analyses. Tableau was used to graphically display the confidence level, number of reviews, health outcomes, and intervention effects. Results: This map encompasses 191 studies, with Mindfulness being the key word that retrieved the highest number of results. Several meditation techniques were evaluated in different contexts, and the confidence levels of 22 studies were high, 84 were moderate, and 82 were low. Two 2 meta-syntheses and 1 integrative review were also included. Most of the studies reported positive effects and a beneficial potential of the practice of meditation. Health outcomes were divided into five groups out of which mental health and vitality, and well-being and quality of life stood out with the largest number of studies. Conclusions: Meditation has been applied in different areas. This Evidence Map intends to be an easy visual tool to access valuable evidence-based information on this complementary therapy for patients, health professionals, and managers.